Regional and demographic determinants of poverty in Brazil - Carlos Azzoni; Andre Souza; Veridiana Nogueira (European Regional Science Association (ERSA), 2004)
The paper identifies the role of regional and demographic determinants of poverty in Brazil. We first estimate the probability of a household being classified as poor or indigent. We then apply decomposition techniques to identify the role of demographic variables (family size, parent's education, etc.) and of regional variables in explaining those probabilities. We found out that parent's education is the most important determinant, but regional aspects also play a role in determining poverty across states in Brazil.
Keywords: 330